PROGRAM DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI JAWA TENGAH DALAM MEMINIMALISIR ANGKA PUTUS SEKOLAH DI SEKOLAH LUAR BIASA (SLB) - Angela, Renyta Syifa; Maulida, Azka Alvira (Universitas Stikubank, 2024)
The purpose of writing this article is to analyse the factors that cause dropout for children with special needs, as well as the programs and role of the education and culture office of Central Java province in minimising dropout rates in special schools (SLB) The research method used in this article is descriptive empirical method, namely research by going directly to the field and then analysing the results of the research. The data sources used in this article consist of primary data sources and secondary data sources. In particular, the factors that cause dropout rates in slb include economic factors, distance factors, parental factors and environmental factors. The Central Java Provincial Education and Culture Office is the education policy maker in the Central Java Province area. In carrying out its policy, the Central Java Provincial Education and Culture Office has the authority to create, implement and monitor the implementation of education. The Central Java Provincial Education and Culture Office also plays an important role in the implementation of various education and culture programmes. The Central Java Provincial Office of Education and Culture in its efforts to minimise dropout rates in slb has several programmes, namely the construction of new school units, pip and bsm assistance, and improving the quality of education in SLB. Keywords: Education and Culture Office Programmes, Dropout, Special Schools (SLB)